THE EFFECTIVENESS OF QUESTION WORD USAGE IN TEACHING SPEAKING AT LANGUAGE CENTER PARE KEDIRI - Umam, Izul (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
Speaking is one of the most difficult aspects for students to master. Students need more practice to master speaking skill. Question word usage can be one of the solutions to stimulate students’ critical thinking in speaking in order the students can make sentence properly. This research aimed (1) to analyze the students’ speaking at experimental class which has been taught by using question word, (2) to analyze the students’ speaking at control class which has not been taught by using question word, (3) to analyze the result between students’ speaking at experimental and control class and (4) to analyze the effectiveness of using question word in teaching speaking. The sample of this study was 37 students taken from the third month those of Language Center Pare Kediri, which were 19 students as experimental class and 18 students as controlled class. They were the students of English Master Program who were in the third month study at Language Center Pare. The method used in this research was a quantitative method. The research results showed that question word or questioning strategy helped the students to achieve a greater improvement on their speaking esspecially their critical thinking in speaking. The result of this research can bring new views and knowledge which can be spread up to other teachers.